1982
DOI: 10.1051/jphys:01982004304059100
|View full text |Cite
|
Sign up to set email alerts
|

An adjustment of the Ne*2(3P0,2-1S 0) potentials to thermal-energy scattering data

Abstract: 2014 On présente ici une recherche semi-empirique des potentiels du dimère Ne*2, pour les états se dissociant en Ne(3P0,2) + Ne(1S0). Partant des potentiels ab initio calculés par Cohen et Schneider, on a déterminé une modification 2014 aussi faible que possible et restreinte au seul domaine des distances intermédiaires (4-10 u.a.) 2014 conduisant à un accord amélioré de la théorie et des expériences effectuées aux énergies thermiques. La modification proposée n'affecte que l'état 303A3u+. Il en résulte, après… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The result of the latter calculation is consistent with the result of a quantum-mechanical calculation by Leung et al [13]. However, the comparison of the calculated optical-absorption shift at the surface with experimental data [26], as well as scattering data obtained by Colomb de Daunant et al [27], showed that V CS is too repulsive at intermediate distances (3-5 Å). Also the desorption energies from our calculation (0.33 eV), which may also be regarded as a test for the validity of the repulsive part of the potential, are larger than the measured values for the 3 P 2 state.…”
supporting
confidence: 87%
“…The result of the latter calculation is consistent with the result of a quantum-mechanical calculation by Leung et al [13]. However, the comparison of the calculated optical-absorption shift at the surface with experimental data [26], as well as scattering data obtained by Colomb de Daunant et al [27], showed that V CS is too repulsive at intermediate distances (3-5 Å). Also the desorption energies from our calculation (0.33 eV), which may also be regarded as a test for the validity of the repulsive part of the potential, are larger than the measured values for the 3 P 2 state.…”
supporting
confidence: 87%
“…A good realization of these criteria can be obtained with a combination of a Born- In the lowest part of the potential well this Morse potential nearly has the same shape as the 3X: potential calculated by Grein et al [24]. I n the outer region it is very similar to the 3Xi potential of Colomb de Daunant et al [25] (see Fig. 2).…”
Section: Tha Potential Curvesmentioning
confidence: 77%
“…have modified the CS potentials and have calculated, by a Jeffreys-Wentzel-Kramers-Brillouin (JWKB) approximation, the scattering amplitudes/ g and/ u (symmetric and antisymmetric), in good agreement with the observed cross sections. 12 We used here the metastability-exchange cross section v e = i I / u -/g 1 2 and the direct one o d = \ I f u +/ g 1 2 deduced from these calculations. In the case when the colliding atoms are of the same isotopic species, indistinguishability does not allow us to separate the two processes.…”
mentioning
confidence: 99%